An audit on outpatient hysteroscopy – cervical dilatation, failure rates and patient satisfaction - Boyd, Sophie; Lalchandani, S (Clinical Journal of Obstetrics and Gynecology, 2021)
Aims: To audit the use of cervical dilators, local anaesthetic, and failure rates in outpatient hysteroscopy over a two-year period in University Hospital Kerry. To review the experiences of women attending the outpatient hysteroscopy clinic (OHC) over a two-year period in University Hospital Kerry. Methods: Retrospective data review was carried out. Green-top Guideline No. 59: Best Practice in Outpatient Hysteroscopy, published by the Royal College of Obstetricians and Gynaecologists (RCOG), was the standard used for comparison. Results: Two hundred and twenty women were seen over a two-year period. The average age was forty-eight. The most common complaint being of menorrhagia/irregular bleeding per vaginum (PV). Local anaesthetic was used in just under one third of cases of which half required cervical dilatation. Most women reported experiencing mild to moderate levels of discomfort however most would opt for an outpatient hysteroscopic procedure again if required. Discussion/Conclusion: Outpatient hysteroscopy is a well-tolerated and safe procedure. Suitability for outpatient hysteroscopy is not predictable based on parity of menopausal status. Women would elect to undergo outpatient hysteroscopy again if required and this is likely due to several reasons including convenience and lack of requirement for general anaesthetic.